EXISTENCE OF TWO PATHOTYPES OF PHYSALOSPORA TUCUMANENSlS IN COASTAL ANDHRA PRADESH* - M. N. SARMA, S. RAMAPANDU AND (Indian Phytopathology, 2002)
Seventeen isolates of the red rot fungus obtained from infected plants of cane cultivars Co 419, Co 7, CoC 671, Co 62175, CoC 8001, C79126 and one unknown cultivar, from different parts of coastal Andhra Pradesh were inoculated on eight sugarcane cultivars, viz., Co 419, Co 997, Co 62175, Co 975, CoJ 64, Co 7717,.B.0. 91, Co 1148 and two genotypes, Baragua and Khakai to identify the pathotypes present in Andhra Pradesh. Among the 17 isolates studied, eight isolates obtained from cultivars Co 419, Co 62175 and CoC BOO1gave a similar patiern of reaction on the cultivars inoculated, while the other nine isolates from Co 7, COC 671, C. 79126 and the unknown cultivar gave another pattern of reaction. Within the two major pathotypes, three bioiypes in each pathotype were identified. The results clearly indicated the existence of two pathotypes in red rot fungus in coastal Andhra region. Cultivars Co 419, Co 7; Co 62175 and CoJ 64 gave differential reaction with the different pathotypes and appear to be useful as differential hosts.